Boundary element analysis of time-dependent material non-linearity - Chandenduang, Chatrchai (2000)
A two dimensional boundary element method (BEM) formulation and computer program for creep problems based on an initial strain approach has been successfully implemented using Fortran code. Two creep laws which can be used in this program are time hardening and strain hardening. The details of the numerical algorithm are presented using isoparametric quadratic elements to model the boundary with 3-node boundary elements, and to model the interior domain with 8-node quadrilateral cells. The BEM program also covers the variable stress load problems. The creep problems of a square plate, a plate with a circular hole and a plate with a semicircular notch are investigated.